2022
DOI: 10.1152/ajpendo.00401.2021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of the preptin-coding portion of Igf2 impairs pancreatic function in female mice

Abstract: Preptin is a 34-amino acid peptide derived from the E-peptide of pro-insulin-like growth factor 2 and is co-secreted with insulin from β-cells. Little is understood about the effects of endogenous preptin on whole-body glucose metabolism. We developed a novel mouse model in which the preptin portion of Igf2 was genetically ablated in all tissues, hereafter referred to as preptin knockout (KO) and tested the hypothesis that the removal of preptin will lead to a decreased insulin response to a metabolic challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…This fits with our previous data showing that preptin ablation in female mice led to diminished GSIS. (34) In this study, nonfasted blood glucose concentrations were lower in male KO mice than in WT mice at the start and end of the dietary intervention period in the LFD study arm despite the absence of major differences in weight and fat mass. This suggests that preptin deficiency may improve overall physiological glucose regulation in a nonstressed state in males specifically.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…This fits with our previous data showing that preptin ablation in female mice led to diminished GSIS. (34) In this study, nonfasted blood glucose concentrations were lower in male KO mice than in WT mice at the start and end of the dietary intervention period in the LFD study arm despite the absence of major differences in weight and fat mass. This suggests that preptin deficiency may improve overall physiological glucose regulation in a nonstressed state in males specifically.…”
Section: Discussionmentioning
confidence: 54%
“…(59) In contrast, we have been unable to detect preptin in adult mouse serum. (34) Nevertheless, it would be of interest to investigate whether preptin is affected by feeding mice a HFD and whether preptin concentrations are related to any of the bone parameters measured in our study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Multiple sources of preptin secretion besides beta cells, such as the kidneys, liver, salivary gland and mammary tissue, have been found since its discovery [ 1 ]. Female preptin knockout mice exhibit reduced glucose-enhanced insulin secretion, but not males [ 4 ]. Early clinical studies reported higher plasma preptin concentrations in patients with type 2 diabetes mellitus (T2M) compared to patients with impaired glucose tolerance and controls, respectively.…”
Section: Introductionmentioning
confidence: 99%